Interaction between visual working memory and upright postural control in young adults: an event-related potential study based on the n-back paradigm - Shan, Sharui; Hong, Feng; Cui, Liyan; Sun, Chenming; Lu, Jianliang; Chen, Zhuoming; Cheng, Wenwen (Frontiers in Neuroscience, 2024)
As a part of the overall information-processing system of the brain, postural control is related to the cognitive processes of working memory. Previous studies have suggested that cognitive tasks and postural control processes can compete for resources in common brain areas, although there is an “inverted U” relationship between arousal level and behavioral control – the arousal level of individuals changes when performing cognitive tasks. However, the exact neural connections between the two are unclear. This may be related to the nature of cognitive tasks. Some studies believe that posture occupies not only spatial information processing resources but also visual non-spatial information processing resources. Other studies believe that posture control only occupies spatial information processing resources in the central system, but does not occupy non-spatial information processing resources. Previous studies used different cognitive task materials and reached different conclusions. In this study, we used the same visuospatial and non-spatial materials, the n-back visual working memory paradigm, the event-related potential technique to investigate the effects of visuospatial and non-spatial working memory tasks on adolescents’ postural control under different cognitive loads. The results of this study showed that in both visuospatial and non-spatial conditions, the N1 effect of the parieto-occipital lobe was larger during upright posture than in the sitting position (160–180 ms), the P300 effect of the central parieto-occipital region (280–460 ms) was induced by working memory in different postures, and the P300 wave amplitude was higher in the sitting position than in the upright position. We demonstrated that upright postural control enhances early selective attention but interferes with central memory encoding, thus confirming that postural control and visuospatial and non-spatial working memory share brain regions and compete with each other.